Characterization of the novel HLA allele: HLA‐B*15:437 in a Chinese bone marrow donor. (8th June 2020) - Wang, Fang; You, Xuan; Zhang, Wei; He, Ji; Zhu, Faming
Abstract : HLA‐B*15:437 shows one nucleotide difference with B*15:02 at position 814 G>A.